Digital Reading Habits of EFL Learners: Did Online Learning during the Pandemic Covid-19 Enhance the Digital Reading Habit? - Marpaung, Magdalena Br.; Indrawati, Ni Luh Ketut Mas; Suparwa, I Nyoman; Malini, Ni Luh Nyoman Seri (RIRAI Publisher, 2025)
Since the pandemic has been over, a question come asking ‘Did online learning during the pandemic of Covid-19 enhance digital reading habits?’ Answering that inquiry, this study focuses on two questions (1) how are digital reading habits (preference and frequency) of EFL learners? And (2) Why does digital reading habit of EFL learners in that way? This is a qualitative descriptive study. This study collected data by administering written interviews via Google form to 24 informants. There are 15 questions asked to the 24 informants and after analyzing the data, the following findings are found. First, all EFL learners prefer reading digitally either for college assignments, articles, books, or novels. However, due to their preference, EFL learners are reading viral news on social media much more than other reading material. Related to the frequency, the highest frequency of reading is at the level of ‘seldom’ for all of the reading material. So, the digital reading habits of EFL learners are still in poor condition since their preference and frequency are far from accessing scientific articles and books digitally. Answering the second question of the reason for the EFL digital reading habit in that condition, the data analysis comes to the conclusion of learners’ bad digital literacy in accessing scientific articles and books digitally. From the interview questions and the informants' responses, there were found that even though the online learners had been for more than two years, the EFL learners’ digital literacy was in bad condition and so affected the reading preference and frequency in digital.